NORA’A KEKE ORAL TRADITION: KAILI TRIBE DISASTER CONTROL RITUALS IN PALU VALLEY (TRADISI LISAN NORA’A KEKE: RITUAL PENGENDALIAN BENCANA SUKU KAILI DI LEMBAH PALU) - Yunidar Yunidar; Gazali Lembah; Ade Nurul Izatti G Yotolembah; Ulinsa Ulinsa; Muthia Aryuni; Muhammad Ahsan Samad (Jurnal Gramatika, 2022)
Nora'a Keke is a ritual of the cultural tradition of Kaili tribe which is understood to give blood or offerings to ancestral spirits to pour rain to drought-stricken areas due to the long dry. The problem of this research was that it can reveal the implementation procession, symbols, and values contained in the Nora'a Keke ritual. This study aims to determine the process of carrying out the Nora'a Keke ritual. The method used in this research is descriptive qualitative using three data collection techniques, namely: observation, interviews and other supporting documents. Data were analyzed by collecting, reducing, presenting and concluding data. The results showed that the Nora'a Keke ritual process consisted of three stages, namely: (1) the initial stage such as deliberation and opening ceremonies, (2) the core stage, the implementation of the Nora'a Keke ritual and (3) the final stage, eating by following the customs. and Moraego. The important values contained in the Nora'a Keke ritual are: religious, philosophical and ethical values.